Peter Arkoudios (1563–1633): A Greek, and a Herald of Ecclesiastical Unity in Lithuania and Europe - Baronas, Darius (Lietuvos istorijos studijos, 2025)
The present article is a biographical study of the Greek-Rite Catholic priest and theologian Peter Arkoudios (1563–1633). The study employs the theoretical approach of civilisational axes in order to shed more light on the historical significance of this personality, who played a prominent role in the promotion of the ecclesiastical Union of Brest (1596). Data are presented indicating the influence exerted by Arkoudios on both the future bishop Ipatii Potii and on the future martyr Josaphat Kuntsevych. Emphasis is placed on his Greek origin and his profound erudition, i.e., on qualities which could not fail to have an impact on the Ruthenians who traditionally felt a deep respect for Greek theological thought. Questions are raised, the discussion of which will provide a better understanding of the circumstances surrounding why Peter Arkoudios did not pursue an ecclesiastical career in the Polish-Lithuanian Commonwealth. From the traces of his cultural activities preserved in Vilnius, it can be seen that Arkoudios contributed to the dissemination of late Byzantine theological thought among both Catholics and Uniates. In belonging to different worlds, primarily Greek and Roman, he played a significant role as an agent of cultural transfer at the end of the 16th century and the beginning of the 17th century.